Reduction of Lipid Oxidation without Compromising Color: the Role of Pomegranate Peel Extract in Pork Sausages - Bobko, Marek; Mesárošová, Andrea; Lidiková, Judita; Bobková, Alica; Demianová, Alžbeta; Švecová, Terézia; Čeryová, Natália; Jurčaga, Lukáš (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2025)
The modern meat industry is under pressure from customers who demand clean-label products. Also, suspicion about the potentially harmful effect of synthetic antioxidants pushes the industry to come up with natural antioxidant options for their product. Plants rich in polyphenols, like pomegranate, have been at the center of those attempts for several years. Our study incorporated pomegranate peel extract into experimental sausage to determine its potential to delay negative oxidative changes of lipids in meat products. To determine the antioxidant effect of extracts TBARS method was used. Addition of plant-based additions into the meat products could, however, alter sensory properties of final product, such as color. Color of meat products is a highly important trait, as it is the first trait that is perceived by customers. To evaluate these potential changes of extract-enhanced sausages color was measured using spectrophotometer Konica Minolta CM-2600d and results expressed as coordinates in CieLab color space. The negative control showed an increase in malondialdehyde levels of about 134% during the storage. On the other hand, treatments with peel extracts addition saw significantly lower increase in the same period. Regarding color of final products, differences were observed only at the start of the storage period in lightness and yellowness parameters. At the end of storage period, no significant differences were observed, therefore, we could argue that pomegranate peel extract has no negative effect of pork sausage color.